The Effect of Audio Visual Media on Student Learning Outcomes during the Pandemic: Pengaruh Media Audio Visual terhadap Hasil Belajar Siswa pada Masa Pandemi - Oktaviyan, Mochammad Reda; Tirtoni, Feri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe the existence of